PENGUATAN KAPASITAS SUMBER DAYA MANUSIA MELALUI GREEN HUMAN RESOURCE MANAGEMENT DAN INOVASI HIJAU DI CALON KAMPUNG NELAYAN MERAH PUTIH - Roby Sambung; Vivy Kristinae; Erwin Prasetya Toepak; Ani Mahrita; Jonathan Giovanni; Nurlia Eka Damayanti; Kembara Sopather; Normand Armando Lampe; Aprilita Aprilita (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTThis community service activity aimed to strengthen human resource capacity through Green Human Resource Management (GHRM) and green innovation in the prospective Kampung Nelayan Merah Putih located in Tanjung Putri and Sei Ijum Raya Villages, Central Kalimantan. The activity adopted a participatory action research approach involving local communities in every stage, from identification to training evaluation. The program was designed through three integrated components: socialization on green innovation, training on GHRM, and green marketing practice. The training increased participants’ understanding of sustainable human resource management and environmental awareness. The pre-test and post-test results indicated an average knowledge improvement of more than 40 percent, showing a significant shift in participants’ behavior toward environmentally responsible practices. The integration of GHRM and green innovation proved effective in empowering coastal communities, strengthening village institutions, and encouraging the emergence of sustainable economic initiatives. This model demonstrates that environmentally-based capacity building can be replicated in other coastal villages to promote inclusive green and blue economy development.Keywords: Green Human Resource Management, green innovation, green marketing, coastal community, sustainable developmentABSTRAKKegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat kapasitas sumber daya manusia melalui penerapan Green Human Resource Management (GHRM) dan inovasi hijau di Calon Kampung Nelayan Merah Putih yang berlokasi di Desa Tanjung Putri dan Desa Sei Ijum Raya, Kalimantan Tengah. Kegiatan dilaksanakan dengan pendekatan participatory action research yang melibatkan masyarakat secara aktif dalam setiap tahap, mulai dari identifikasi masalah hingga evaluasi pelatihan. Program ini dirancang melalui tiga komponen utama, yaitu sosialisasi tentang inovasi hijau, pelatihan GHRM, dan penerapan green marketing. Hasil kegiatan menunjukkan peningkatan pengetahuan peserta lebih dari 40 persen dan perubahan perilaku menuju praktik ramah lingkungan. Integrasi antara GHRM dan inovasi hijau terbukti efektif dalam meningkatkan kapasitas masyarakat pesisir, memperkuat kelembagaan desa, serta mendorong munculnya inisiatif ekonomi berkelanjutan. Model pelatihan ini dapat direplikasi pada desa pesisir lain untuk mendukung pembangunan hijau dan ekonomi biru yang inklusif.Kata Kunci: Green Human Resource Management, inovasi hijau, green marketing, masyarakat pesisir, pembangunan berkelanjutan